2014
DOI: 10.9799/ksfan.2014.27.4.641
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Obesity Effect of Commercial Kochujang and Fermented Wheat Grain Products in Sprague-Dawley Rats

Abstract: The antiobesity effect of commercial kochujang and fermented wheat grains in Sprague-Dawley (SD) rats was studied. The experiment was consisted of 6 groups. Normal, high fat diet (HFD), HFD+raw wheat grains, HFD+first fermented wheat grains (FFWG, with Aspergillus oryzae) HFD+final fermented wheat grains (FiFWG, fermented more for 30~40 days), and HFD+ commercial kochujang. The results showed that final body weight, weight gain, food efficiency ratio, and adipose tissue weight were markedly decreased by the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…With respect to the functionality of gochujang, various studies have examined its anti-obesity effect (Kim & Lim, 2014;Koo et al, 2008;Shin et al, 2016;Son et al, 2018). Fermented gochujang is reported to have greater anti-obesity effects than nonfermented gochujang (Rhee, Kong, Jung, & Park, 2003;Shin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the functionality of gochujang, various studies have examined its anti-obesity effect (Kim & Lim, 2014;Koo et al, 2008;Shin et al, 2016;Son et al, 2018). Fermented gochujang is reported to have greater anti-obesity effects than nonfermented gochujang (Rhee, Kong, Jung, & Park, 2003;Shin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Gochujang possesses various biological properties, including anti‐atherosclerotic (Cha et al, ; Hyun, No, Lim, Cha, & Choi, ; Lim et al, ), anti‐obesity (Cha et al, ; Choo & Shin, ; Kim & Lim, ; Koo, Seong, Kown, Sohn, & Cha, ; Lee, Cha, Park, & Lee, ; Shin et al, ; Son et al, ; Yang, Kim, Kim, Lee, & Hong, ), anti‐diabetic (Kang et al, ; Kwon et al, ; Yang et al, ), and anti‐cancer (Park, Kong, Jung, & Rhee, ) effects. The major ingredients of gochujang are red pepper, grains (such as white, brown, and glutinous rice, barley, and wheat), and meju (fermented soybean powder).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, it was revealed that 99.25% of the families living in Tokat province consumed tomato paste and 41.85% of them consumed pepper paste (Büyükbay et al, 2009). Another similar type paste of Korea, Gochujang, was reported as a healtier product by reducing fat gain, adipocyte size, serum lipid levels, leptin-secretion, tumor necrosis factor mRNA level (Ahn et al 2006;Kim et al 2014).…”
Section: Introductionmentioning
confidence: 99%